Development of Fraction Puzzle Teka-Teki Media to Improve Mathematical Problem-Solving Ability Students in Elementary School - Dwi Endah Lestari; Wahyudi Wahyudi (Edumaspul: Jurnal Pendidikan, 2023)
This research examines the development of a media entitled "Fraction Puzzle Teka-Teki" with the aim of improving the mathematical problem-solving abilities of 2nd grade elementary school students. This media is designed with an interactive approach to address issues in mathematics education for students with low problem-solving abilities. This research uses Research and Development research with the ADDIE (Analysis, Design, Development, Implementation and Evaluating) development model. The research subjects were the Tingkir Lor 02 Salatiga State Elementary School, the research samples were 2nd grade elementary school students. Validation results from subject matter experts, media experts, and learning experts indicate very high levels of validity, with scores reaching 91.6%, 93.3%, and 75%, respectively with very high category. Media practicality received a percentage of 88% in the very high category from student responses and 92.5% in the very high category from teacher responses. The implementation of the "Fraction Puzzle Teka-Teki" in education is effective, as evidenced by the improvement in post-test scores for second-grade students. Statistical analysis shows significant results (Sig. [2-tailed] = 0.000 < 0.05), indicating an enhancement in mathematical problem-solving abilities following the use of the developed media. Based on these findings, it can be concluded that "Fraction Puzzle Teka-Teki" is a suitable tool for mathematics education and is effective in enh ancing the mathematical problem-solving abilities of students. indicating an enhancement in mathematical problem-solving abilities following the use of the developed media. Based on these findings, it can be concluded that "Fraction Puzzle Teka-Teki" is a suitable for use in mathematics education and is effective in improving the mathematical problem-solving abilities of 2nd grade elementary school student.